Narrating psychological realism and time temporality: A critical study of Shahad Al Rawi’s The Baghdad Clock - Saad Aziz, Ahmed (Research Journal in Advanced Humanities, 2025)
Psychological realism in contemporary prose fiction focuses on the internal life of characters, emphasizing subjective experiences and memory. Time, in such fiction, transcends its mechanical measurement and is instead understood through psychological perception. This paper examines The Baghdad Clock (2018) by Shahad Al Rawi through the lens of Paul Ricoeur’s theory in Time and Narrative, exploring how the novel disrupts linear temporality to reflect the psychological trauma of war. The study argues that Al Rawi constructs a non-linear narrative where the past, present, and future converge, creating a temporal structure that mirrors Iraq’s national trauma. Utilizing a structural approach and integrating theories of psychological realism and narrative temporality, the study reflects on how memory, trauma, and time shape both personal and collective identities in post-2003 Iraqi fiction. The significance of this study lies in its exploration of temporal disorientation and narrative innovation as responses to prolonged conflict, trauma, and historical rupture in Iraq’s recent past.